'Trusty Bess': the Definitive Origins and History of the term 'Brown Bess'. (2nd January 2017) - Ferguson, Jonathan
Abstract : The aim of this article is to settle once and for all the question of the term 'Brown Bess', as applied to the British soldier's musket. The specific origin and meaning of this obviously affectionate nickname has long confounded arms and armour scholars, re-enactors, and collectors alike. As a result, various possible solutions have been offered. The article outlines the historical usage of the name, including earlier written references not widely known in the field. The scope of the term is also addressed, using period sources to demonstrate what 'Brown Bess' meant to those who actually used the name historically. The many false etymologies of the name are assessed and found wanting or 'debunked' outright. Finally, drawing upon existing research from the field of linguistics, the article details the real meaning behind 'Brown Bess' the firearm and places 'her' in a wider sociohistorical context.